2006
DOI: 10.1016/j.bbalip.2006.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Membrane binding domains

Abstract: Eukaryotic signaling and trafficking proteins are rich in modular domains that bind cell membranes. These binding events are tightly regulated in space and time. The structural, biochemical, and biophysical mechanisms for targeting have been worked out for many families of membrane binding domains. This review takes a comparative view of seven major classes of membrane binding domains, the C1, C2, PH, FYVE, PX, ENTH, and BAR domains. These domains use a combination of specific headgroup interactions, hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 79 publications
(96 reference statements)
1
133
0
1
Order By: Relevance
“…In solution, it would be available for membrane binding. We speculated that these residues comprised either a docking site for another protein or, by analogy to other membrane-binding domains (3,17), a hydrophobic membrane anchor. Such anchor regions occurs on FYVE, C1, PX, and ENTH domains and others and increase affinity for membraneembedded lipids by allowing the protein itself to embed into the membrane (3,17).…”
Section: Resultsmentioning
confidence: 99%
“…In solution, it would be available for membrane binding. We speculated that these residues comprised either a docking site for another protein or, by analogy to other membrane-binding domains (3,17), a hydrophobic membrane anchor. Such anchor regions occurs on FYVE, C1, PX, and ENTH domains and others and increase affinity for membraneembedded lipids by allowing the protein itself to embed into the membrane (3,17).…”
Section: Resultsmentioning
confidence: 99%
“…My aim in this review is to introduce general principles governing the lipid binding and cellular localization of some of the lipid-binding domains. The description and examples used are selective, and I refer the reader to other compelling reviews (4,(9)(10)(11) Figure 1 summarizes some of the common properties of these lipid-binding domains. All intracellular membranes contain a varying degree of anionic lipids, and a majority of lipid-binding domains contain cationic surfaces, at least locally.…”
Section: : S299-s304mentioning
confidence: 99%
“…The Spir proteins encode a modified FYVE zinc finger membrane-binding domain at the C-terminal end (Kerkhoff et al, 2001). FYVE zinc fingers are typically found in proteins involved in membrane trafficking (Hurley, 2006). Early on after the discovery of Spir proteins, transient expression studies in NIH 3T3 fibroblast cells showed that the actin nucleators accumulate at vesicle membranes where they induce the accumulation of filamentous actin (Otto et al, 2000).…”
Section: Functional Cooperation Of Spir/ Formin-2 Rab11 and Myosin mentioning
confidence: 99%